2022
DOI: 10.3389/fendo.2022.1013959
|View full text |Cite|
|
Sign up to set email alerts
|

Metabolomics analysis of stool in rats with type 2 diabetes mellitus after single-anastomosis duodenal–ileal bypass with sleeve gastrectomy

Abstract: BackgroundSingle-anastomosis duodenal-ileal bypass with sleeve gastrectomy (SADI-S) is one of the most effective bariatric procedures in the treatment of type 2 diabetes mellitus (T2DM). However, the mechanisms by which SADI-S improves T2DM are not well-known.ObjectiveTo explore the effects of SADI-S on metabolites in the stool of rats with T2DM.MethodsTwenty rats were fed on high-fat diet and administered with a low-dose (30mg/kg) of streptozotocin to establish T2DM models. The rats were then randomly assigne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 49 publications
0
4
0
Order By: Relevance
“…Fecal metabolites are the products of complex metabolic activities of gut microbiota in the body, and also serve as a bridge for the interaction between the host and intestinal microorganisms. Our previous study demonstrated that the level of fecal SCFA in T2D rats significantly increased after SADI-S (Wang et al, 2022). SCFA can stimulate ileocolic L cells to secrete GLP-1, promoting insulin secretion and islet β-cell proliferation.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Fecal metabolites are the products of complex metabolic activities of gut microbiota in the body, and also serve as a bridge for the interaction between the host and intestinal microorganisms. Our previous study demonstrated that the level of fecal SCFA in T2D rats significantly increased after SADI-S (Wang et al, 2022). SCFA can stimulate ileocolic L cells to secrete GLP-1, promoting insulin secretion and islet β-cell proliferation.…”
Section: Discussionmentioning
confidence: 97%
“…BCAA levels were significantly reduced in patients with T2D after bariatric surgery ( Arora et al, 2015 ; Luo et al, 2016 ). Previous study ( Wang et al, 2022 ) found that the elevated levels of BCAA are associated with the increased abundance of bacteria that synthesize BCAA such as Prevotella ( Pedersen et al, 2016 ). Consistent with the above findings, our previous ( Wang et al, 2022 ) and present study found that the levels of BCAA and the abundance of Prevotella in T2D rats significantly decreased after SADI-S.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…SADI-S can affect the metabolism of bile acids. In rats with type 2 diabetes mellitus treated with SADI-S, the levels of lithocholic acid and cholic acid were markedly improved, while the levels of taurochenodeoxycholic acid and deoxycholic acid were markedly decreased ( 68 ). The regulation of bile acid metabolism by SADI-S is beneficial for treating type 2 diabetes mellitus.…”
Section: Bariatric Surgery and Gut Microbiota Metabolitesmentioning
confidence: 99%